Differential Diagnosis in Hypophysitis: First Report on a Spindle Cell Rhabdomyosarcoma of the Pituitary Gland - Ahmeti, Hajrullah; Jüttner, Eva; Röcken, Christoph; Jansen, Olav; Laudes, Matthias; Synowitz, Michael (Journal of Neurological Surgery Part A: Central European Neurosurgery, 2021)
Pituitary gland metastases are very rare. Most patients with pituitary gland metastases are asymptomatic; therefore, most cases of this disease are diagnosed during autopsies. Moreover, the four most common primary tumors that metastasize to the pituitary gland are breast, lung, thyroid, and renal carcinomas. We present a very rare case of pituitary metastasis of spindle cell rhabdomyosarcoma (RMS). Our patient presented with headache, visual disorder, panhypopituitarism, and diabetes insipidus. Due to tumor expansion, resection was not possible, so diagnosis was confirmed by biopsy, and chemotherapy and irradiation were administered. Our patient showed widespread spindle cell RMS, which harbors a mutation of myogenic differentiation 1 (MYOD1) and is associated with a poor prognosis. Even high-risk patients can show a remission after chemotherapy and irradiation. In the cases with indistinct lesions in the sella region, pituitary metastasis should always be considered.
Keywords: pituitary metastases; rhabdomyosarcoma; panhypopituitarism; mutation of myogenic differentiation 1